The expression that correctly shows the sum of opposite numbers is:
\((-25) + 25 = 0\)
This expression demonstrates that when you add a number and its opposite (in this case, \(-25\) and \(25\)), the result is zero.
Responses
(−25)+(−25)=−50
left parenthesis negative 25 right parenthesis plus left parenthesis negative 25 right parenthesis equals negative 50
(−25)+25=50
left parenthesis negative 25 right parenthesis plus 25 equals 50
(−25)+25=0
left parenthesis negative 25 right parenthesis plus 25 equals 0
(−25)+(−25)=0
1 answer
The expression that correctly shows the sum of opposite numbers is:
\((-25) + 25 = 0\)
This expression demonstrates that when you add a number and its opposite (in this case, \(-25\) and \(25\)), the result is zero.